Integrated Supply Chain Planning in Chemical Industry: Potentials of Simulation in Network Planning - Kirschstein, Thomas (Springer, 2015)
Thomas Kirschstein provides an overview on methods and approaches for planning and optimizing large-scale chemical production networks. The focus is on an integrated modelling of chemical production processes, logistical processes as well as environmental effects. Therefore, a hybrid simulation framework is designed taking into account time series models for modelling chemical production processes, linear optimization models for describing logistical processes as well as stochastic processes for modelling environmental effects.